Analisis Faktor-Faktor Yang Mempengaruhi Kebijakan Dividen Koperasi One Satoric Mandiri di Kabupaten Semarang - Harefa, Dedi Saputra; Hendrajaya, Hendrajaya (Mahesa Research Center, 2025)
This article aims to analyze the factors influencing the dividend policy or the distribution of the Remaining Operating Results (SHU) at One Satoric Mandiri Cooperative in Semarang Regency. The study focuses on how internal and external factors interact within the decision-making process for SHU distribution. A qualitative research approach was used, with data collected through in-depth interviews, non-participatory observations, and document analysis. The data were analyzed using an interactive analysis model involving data reduction, presentation, and conclusion drawing. The findings show that the cooperative’s dividend policy is influenced by internal factors such as financial performance, member participation, decision-making mechanisms through the Annual Member Meeting (RAT), and reserve fund requirements. External factors include government regulations and regional economic conditions. The study concludes that the dividend policy at One Satoric Mandiri Cooperative results from a participatory and transparent decision-making process oriented toward sustainability. Cooperatives that can balance economic, social, and regulatory aspects are more likely to strengthen member trust and enhance long-term welfare.